La Arte inglese oggi 1960-76 = English Art Today 1960-76 : Parte seconda = Part two. - Exhibition. Arte inglese oggi 1960-76 = English Art Today 1960-76. Palazzo Reale Milano. 1976-02 t/m 1976-05; Arnatt, Keith; Art & Language; Brisley, Stuart; Burgin, Victor; Cameron, Shirley; Cork, Richard; Curtis, David; Dunford, Mike; Dye, David; Fanni, Cosey; Gidal, Peter; et al. (Milano : Electa Editrice Milano Palazzo Reale Milano, 1976)
Arnatt, Keith ; Art & Language ; Burgin, Victor ; Brisley, Stuart ; Cameron, Shirley ; Coum Transmissions ; Dunford, Mike ; Dye, David ; Gidal, Peter ; Gilbert & George ; Grice, Malcolm Le ; Haselden, Ron ; Haslam, Leslie ; Head, Tim ; Hilliard, John ; Keen, Jeff ; Long, Richard ; McCall, Anthony ; Miller, Roland ; Nicolson, Annabel ; Raban, William ; Rhodes, Liz ; Sherwin, Guy ; Stezaker, John ; Welsby, Chris
biog., bibliog., filmog. per kunstenaar
Engels
Italiaans
boek
Keywords: Groot-Brittannië